2018
DOI: 10.1007/s00417-018-4176-5
|View full text |Cite
|
Sign up to set email alerts
|

Alteration of lens and retina textures from mice embryos with folic acid deficiency: image processing analysis

Abstract: Purpose: Folic Acid (FA) is an essential vitamin for embryonic development. It plays particularly a critical role in RNA, DNA, and protein synthesis. On the other hand, the collagen IV and laminin-1 are important proteins during embryonic development. This study was done to find if FA-deficiency at a short and a long-term in mothers could alter the tissue texture of retina and lens of the progeny. Methods: Collagen IV and laminin-1 were localized by immunohistochemistry in the lens and retina of the FA-deficie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 40 publications
0
10
0
Order By: Relevance
“…Moreover, folate deficiency seems to be related to an alteration of mitochondrial metabolism, due to a modification of the folate pathway which would involve the electron transport chain, and thereby reduce ATP production, in a similar way as it happens in Leber hereditary optic neuropathy [23]. Other hypotheses have been developed thanks to animal models: for example, folate concentration might be associated to macrophage-mediated inflammatory response [24], and also it could also affect the composition of extracellular matrix both in the retina and in lens [25].…”
Section: Folic Acid (Vitamin B9)mentioning
confidence: 99%
“…Moreover, folate deficiency seems to be related to an alteration of mitochondrial metabolism, due to a modification of the folate pathway which would involve the electron transport chain, and thereby reduce ATP production, in a similar way as it happens in Leber hereditary optic neuropathy [23]. Other hypotheses have been developed thanks to animal models: for example, folate concentration might be associated to macrophage-mediated inflammatory response [24], and also it could also affect the composition of extracellular matrix both in the retina and in lens [25].…”
Section: Folic Acid (Vitamin B9)mentioning
confidence: 99%
“…In previous studies, we have observed that maternal dietary FAD alters the expression of collagen IV and laminin‐1 into the lens and retina, and also reveals disorganization of fibers/cells orientation. [ 28, 29 ]…”
Section: Resultsmentioning
confidence: 99%
“…This may be due to increase in protein aggregates or highly concentrated proteins in lens fiber cells, and it would be compatible with previous findings where we showed an alteration in the expression and arrangement of ECM proteins. [ 28, 29, 40, 41 ] It is known that cataractogenesis is caused by light scattering due to random fluctuations in the refractive index. [ 42 ] These fluctuations may occur because of differences in the structure of the lens fiber cells involving alterations in the cell membrane, minimal changes in intercellular spacing, changes of structure within the cytoplasm or protein aggregation.…”
Section: Resultsmentioning
confidence: 99%
“…This technique is also used for identifying the number of changes developed in the pattern and textures of any surface. 84…”
Section: Autocorrelation Functionmentioning
confidence: 99%